Human dirofilariasis - Kern, Thomas (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1998)
Human infections with zoonotic filariae are frequently observed throughout theworld. Filarial worms of the genus dirofilaria are well known nematodes of carnivorous mammals and can be found in Asia and Africa as well as in the United States and in Europe. Human dirofilariasis is an infection caused by filarial nematodes of the genus dirofilaria. Man is only occasionally infected. The parasite's cycle involves uptake of microfilariae from the peripheral blood circulation of infected dogs or cats by mosquitos (Anopheles,Culex, Aedes). Dirofilariasis is transmitted by haematophagous arthropods to man, in whom the nematodes usually die before reaching sexual maturity. Identification of dirofilariae from tissue sections is difficult, but knowledge of the parasite's geographic distribution and patients travel history may be helpful.
Keywords: Dirofilaria; Dirofilariasis; Host-parasite relations